Pengetahuan Dewan Tentang Anggaran Dalam Pengawasan Keuangan Daerah (APBD) Di Kabupaten Sidoarjo: Council's Knowledge of Budgets in Regional Financial Supervision (APBD) in Sidoarjo Regency - Dewi, Santi Rahma; Sinduwiatmo, Kukuh; Biduri, Sarwenda (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to find out how the board's knowledge about the budget in implementing regional financial supervision (APBD).This research was conducted with qualitative methods by presenting elements of questions regarding the board's knowledge of budget and regional financial supervision. Methods of gathering information using interviews and documentation to members of the Sidoarjo Regency council.The results of this study indicate that board members understand the process of determining the budget carried out by the executive, so that they can supervise and control the implementation of the APBD in Sidoarjo Regency. And expect follow-up from the executive on recommendations that have been given by the legislature where so far there has been no follow-up done